2017
DOI: 10.1016/j.jcmg.2016.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Plaque Lipid Content and Fibrous Cap Status Predict Systemic CV Outcomes

Abstract: Objectives We sought to investigate whether and what carotid plaque characteristics predict systemic cardiovascular outcomes in patients with clinically established atherosclerotic disease. Background Advancements in atherosclerosis imaging have allowed assessment of various plaque characteristics, some of which are more directly linked to the pathogenesis of acute cardiovascular events compared to plaque burden. Methods As part of an event-driven clinical trial (AIM-HIGH), subjects with clinically establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 35 publications
2
55
0
1
Order By: Relevance
“…Imaging protocol. Carotid bifurcation MRI was performed at 3 T with a carotid phase-array surface 6-channel coil (Neocoil LLC, Pewaukee, WI, USA) using a previously described multi-contrast protocol 26 . In brief, the sequences included 3D time-of-flight MR angiography (TOF-MRA), a 3D black-blood sequence optimized to detect IPH (magnetization-prepared rapid acquisition gradient echo, MPRAGE), 2D pre-contrast black-blood T1 weighting (T1W), 2D T2 weighting (T2W), and contrast-enhanced 2D black-blood T1W (CE-T1W).…”
Section: Study Populationmentioning
confidence: 99%
“…Imaging protocol. Carotid bifurcation MRI was performed at 3 T with a carotid phase-array surface 6-channel coil (Neocoil LLC, Pewaukee, WI, USA) using a previously described multi-contrast protocol 26 . In brief, the sequences included 3D time-of-flight MR angiography (TOF-MRA), a 3D black-blood sequence optimized to detect IPH (magnetization-prepared rapid acquisition gradient echo, MPRAGE), 2D pre-contrast black-blood T1 weighting (T1W), 2D T2 weighting (T2W), and contrast-enhanced 2D black-blood T1W (CE-T1W).…”
Section: Study Populationmentioning
confidence: 99%
“…Zavodni et al [20] showed that a lipid core at CMR imaging confers increased risk for subsequent cardiovascular events in asymptomatic individuals. Sun et al [21] reported that high lipid content (HR per one-standarddeviation increase in % lipid core volume: 1.57, P = 0.002) in carotid plaques was strongly associated with the cardiovascular outcomes. The LRNC within atherosclerotic plaque, particularly its size, has been believed to be a key feature of vulnerable plaque [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Third, in the present study, the size of the intraplaque compositions of co-existing intracranial and extracranial artery atherosclerosis was not assessed. Previous evidences showed that the size of LRNC [18,21] and IPH [18] was associated with future vascular events. Fourth, the longitudinal coverage of current carotid imaging protocol is 32 mm centered to carotid bifurcation.…”
Section: Limitationsmentioning
confidence: 94%
“…The characteristics of carotid plaque provided by plaque imaging on MR can serve a surrogate marker for risk management of patients with atherosclerosis [5]. The characteristics of carotid plaque such as intraplaque hemorrhage, calcification, and lipid-rich necrotic core are evaluated by threedimensional (3D) T1-weighted fast spin echo (T1-FSE) in combination with T2WI, time-of-flight MR angiography, magnetization-prepared rapid acquisition gradient echo sequences [6].…”
Section: Sensing T1-space Introductionmentioning
confidence: 99%